Hydrogen absorption material, preparation method thereof and battery
By using sealant materials containing alkenyl, alkynyl and phenyl groups in nickel-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen-hydrogen Improve safety and stability.
Patent Information
- Application Number
- CN202411850219.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The hydrogen generated by nickel-hydrogen batteries and nickel-zinc batteries during overcharging or floating charging cannot be effectively absorbed, resulting in battery expansion, liquid leakage and safety issues, limiting their promotion in high-end applications.
A hydrogen absorption material is used, including a sealant and a hydrogen absorption organic substance and a catalyst distributed in the sealant. The hydrogen absorption organic substance contains alkenyl, alkynyl and phenyl groups. The catalyst is a carbon-supported palladium catalyst by placing it with the sealant. Mix to form a new sealant to provide sealing and insulation effects and promote hydrogen absorption.
Effectively prevent the battery from expanding and leaking liquid, improve the safety of the battery, ensure the uniform distribution of hydrogen-absorbing organic matter and catalyst in the sealant, avoid free movement and potential damage, and significantly improve the stability and reliability of the battery.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a hydrogen absorbing material and a preparation method thereof, and a battery. Background Art
[0002] NiMH batteries will continuously generate hydrogen during overcharging or floating charging. When the hydrogen accumulates to a certain level, the explosion-proof ball in the battery design will automatically open to release the gas to prevent the danger caused by excessive pressure inside the battery. However, this process is often accompanied by electrolyte leakage, which not only pollutes the environment, but may also corrode the power source materials, further exacerbating the damage to the equipment.
[0003] What is more serious is that the negative active materials of the emerging aqueous nickel-zinc battery, zinc and zinc oxide, tend to spontaneously react in alkaline electrolytes and release a large amount of hydrogen. Since this hydrogen cannot be effectively absorbed, it will continue to accumulate inside the battery, causing the battery volume to expand, height changes, and even leakage. These problems not only affect the stability and reliability of the battery, but also greatly limit its promotion and use in high-end applications. Summary of the invention
[0004] The embodiments of the present invention provide a hydrogen absorbing material and a preparation method thereof, and a battery to solve the problem that a large amount of hydrogen is generated in a nickel-hydrogen battery or a nickel-zinc battery, causing battery expansion and leakage, thereby achieving the effect of improving battery safety.
[0005] Specifically, the present invention provides a hydrogen absorbing material, including a sealant, a hydrogen absorbing organic substance distributed in the sealant, and a catalyst, wherein the hydrogen absorbing organic substance contains one or more of alkenyl, alkynyl and phenyl groups; and the catalyst is used to increase the reaction rate of the hydrogen absorbing organic substance with hydrogen.
[0006] Optionally, the hydrogen absorbing organic matter is selected from C9~C 22 Benzene derivatives; And / or, the catalyst is selected from carbon-supported palladium catalyst.
[0007] Optionally, the hydrogen absorbing organic matter is selected from one or more of 1,4-bis(phenylethynyl)benzene, 1,4-diphenylbutadiyne and phenyl propargyl ether.
[0008] Optionally, the mass ratio of the catalyst to the hydrogen absorbing organic matter is 1:(1-5); The mass ratio of the catalyst to the sealant is 1:(20-150).
[0009] Optionally, the mass ratio of the catalyst to the hydrogen absorbing organic matter is 1:(2.5-3.5); The mass ratio of the catalyst to the sealant is 1:(20-60).
[0010] Optionally, the sealant includes one of polyurethane glue and organic silicone glue.
[0011] The present invention also provides a method for preparing the hydrogen absorbing material according to any one of the above items, comprising the following steps: grinding the hydrogen absorbing organic matter and the catalyst to obtain a hydrogen absorbing mixture; The hydrogen absorbing mixture is added into the sealant and stirred to obtain the hydrogen absorbing material.
[0012] Optionally, the grinding is performed in an inert gas; And / or, the grinding time is 5-8h; And / or, the stirring temperature is 70-90° C., the stirring time is 1-2 h, and the stirring speed is 40-80 rpm / min.
[0013] The present invention also provides a battery, comprising a battery cell and a hydrogen absorbing material as described in any one of the above items; the hydrogen absorbing material is coated on the insulating sheet of the battery cell, the bottom plate of the positive cap and / or the connection position between the electrode sheet and the electrode ear of the battery cell.
[0014] The beneficial effects of the present invention are: The hydrogen absorbing material provided by the present invention is used in nickel-hydrogen batteries or nickel-zinc batteries, and the alkenyl, alkynyl or phenyl groups in the hydrogen absorbing organic matter can react with the hydrogen generated inside the battery to prevent the battery from swelling and leaking. Furthermore, the hydrogen absorbing material is mixed with the hydrogen absorbing organic matter, the catalyst and the sealant, which not only gives it the function of a new type of sealant, so that it can provide sealing and insulation effects, but also play a hydrogen absorbing role; moreover, this mixing method also ensures that the hydrogen absorbing organic matter and the catalyst are evenly distributed in the sealant, thereby avoiding their free movement inside the battery and potential damage risks. DETAILED DESCRIPTION
[0015] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0016] An embodiment of the present invention provides a hydrogen absorbing material, comprising a sealant, a hydrogen absorbing organic substance distributed in the sealant, and a catalyst, wherein the hydrogen absorbing organic substance contains one or more of an alkene group, an alkynyl group, and a phenyl group; and the catalyst is used to increase the reaction rate of the hydrogen absorbing organic substance with hydrogen.
[0017] The hydrogen absorbing material provided by the present invention is used in nickel-hydrogen batteries or nickel-zinc batteries, and the alkenyl, alkynyl or phenyl groups in the hydrogen absorbing organic matter can react with the hydrogen generated inside the battery to prevent the battery from swelling and leaking. Furthermore, the hydrogen absorbing material is mixed with the hydrogen absorbing organic matter, the catalyst and the sealant, which not only gives it the function of a new type of sealant, so that it can provide sealing and insulation effects, but also play a hydrogen absorbing role; moreover, this mixing method also ensures that the hydrogen absorbing organic matter and the catalyst are evenly distributed in the sealant, thereby avoiding their free movement inside the battery and potential damage risks.
[0018] In one embodiment of the present invention, the hydrogen absorbing organic matter is selected from C9~C 22 The hydrogen absorbing organic matter is selected from one or more of 1,4-bis(phenylethynyl)benzene, 1,4-diphenylbutadiyne and phenyl propargyl ether.
[0019] In one embodiment of the present invention, the catalyst is a carbon-supported palladium catalyst; further, the hydrogen-absorbing organic matter is 1,4-bis(phenylethynyl)benzene. Since the catalyst is a carbon-supported palladium catalyst, the carbon provides a huge active surface area for adsorbing hydrogen in the environment, while the palladium performs a catalytic function to promote the decomposition of hydrogen (H2) into two hydrogen atoms (H). As a hydrogen-absorbing organic matter, 1,4-bis(phenylethynyl)benzene can undergo an irreversible hydrogenation reaction with hydrogen atoms catalyzed by palladium to ensure that hydrogen is effectively absorbed. It is worth noting that each 1,4-bis(phenylethynyl)benzene molecule contains two acetylenic bonds (C≡C). Theoretically, 1 mol of this compound can absorb up to 4 mol of hydrogen, and the potential for absorbing hydrogen is significant. The reaction of 1,4-bis(phenylethynyl)benzene with hydrogen is as follows: .
[0020] In one embodiment of the present invention, the mass ratio of the catalyst to the hydrogen absorbing organic matter is 1: (1-5); if the ratio of the hydrogen absorbing organic matter is too low, the relative ratio of the catalyst is too high, and the catalyst (carbon-supported palladium catalyst) contains precious metals, which are relatively expensive, and excessive use will directly increase production costs; if the ratio of the hydrogen absorbing organic matter is too high, the reaction rate may be significantly slowed down, reducing the hydrogen absorption efficiency. Specifically, the mass ratio of the catalyst to the hydrogen absorbing organic matter is 1: 1, 1: 1.5, 1: 2, 1: 2.5, 1: 3, 1: 3.5, 1: 4, 1: 4.5 or 1: 5. Preferably, the mass ratio of the catalyst to the hydrogen absorbing organic matter is 1: (2.5-3.5), and more preferably 1: 3.
[0021] In one embodiment of the present invention, the mass ratio of the catalyst to the sealant is 1: (20~150). Since the catalyst and the hydrogen absorbing organic matter are matched in a specific ratio, if the sealant ratio is too low, the relative ratio of the catalyst to the hydrogen absorbing organic matter is too high, which is easy to affect the adhesion and sealing performance of the sealant; if the sealant ratio is too high, the relative ratio of the catalyst to the hydrogen absorbing organic matter is too low, reducing the hydrogen absorption effect. Specifically, the mass ratio of the catalyst to the sealant is 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140 or 1:150. Preferably, the mass ratio of the catalyst to the sealant is 1: (20~60).
[0022] The sealant includes one of polyurethane glue and organic silica gel. Both polyurethane glue and organic silica gel have the characteristics of strong adhesion and good air permeability, so they can provide sealing and insulation effects, and allow hydrogen to enter the sealant to react with hydrogen-absorbing organic matter to play a hydrogen-absorbing role.
[0023] The embodiment of the present invention further provides a method for preparing a hydrogen absorbing material, which is used to prepare the hydrogen absorbing material in any of the above embodiments. The preparation method comprises the following steps: The hydrogen absorbing organic matter and the catalyst are ground in an inert gas to obtain a hydrogen absorbing mixture; the grinding time is 5-8 hours to fully mix the hydrogen absorbing organic matter and the catalyst, avoid agglomeration of the hydrogen absorbing mixture and the catalyst, and improve the catalytic efficiency.
[0024] The hydrogen absorbing mixture is added to the sealant and stirred to obtain the hydrogen absorbing material. The stirring temperature is 70-90° C., the stirring time is 1-2 hours, and the stirring speed is 40-80 rpm / min.
[0025] An embodiment of the present invention also provides a battery, which is a nickel-metal hydride battery or a nickel-zinc battery, comprising a battery cell and the hydrogen absorbing material in any of the above embodiments, so as to have all the effects of the hydrogen absorbing material; the hydrogen absorbing material is coated on the insulating sheet of the battery cell, and / or at the connection position between the electrode sheet and the electrode ear of the battery cell.
[0026] The present invention is further described below by way of examples.
[0027] Example 1 One part of carbon-supported palladium catalyst and 3 parts of 1,4-bis(phenylethynyl)benzene were added into an agate mortar and ground thoroughly to obtain a hydrogen absorption mixture; the process was carried out in a glove box filled with inert gas, and the grinding time was 8 hours.
[0028] The ground hydrogen absorbing mixture was added into 40 parts of polyurethane sealant, and then fully stirred on a magnetic stirrer at 80° C. to obtain a hydrogen absorbing material.
[0029] Simply dip the insulating sheet at the bottom of the nickel-hydrogen battery cell into the hydrogen absorbing material, and evenly apply the hydrogen absorbing material to the welding position between the positive electrode ear and the positive electrode sheet and the bottom plate of the positive electrode cap. After applying, use a purple light to heat it to accelerate the solidification and fixation of the hydrogen absorbing material.
[0030] Example 2 The difference between Example 2 and Example 1 is that the amount of 1,4-bis(phenylethynyl)benzene is 0.5 parts.
[0031] Example 3 The difference between Example 3 and Example 1 is that the amount of 1,4-bis(phenylethynyl)benzene is 1 part.
[0032] Example 4 The difference between Example 4 and Example 1 is that the amount of 1,4-bis(phenylethynyl)benzene is 5 parts.
[0033] Example 5 The difference between Example 5 and Example 1 is that the amount of 1,4-bis(phenylethynyl)benzene is 7 parts.
[0034] Example 6 The difference between Example 6 and Example 1 is that 1,4-diphenylbutadiyne is used to replace 1,4-bis(phenylethynyl)benzene.
[0035] Example 7 Example 7 differs from Example 1 in that 1,4-bis(phenylethynyl)benzene is replaced by phenyl propargyl ether.
[0036] Example 8 The difference between Example 8 and Example 1 is that the amount of polyurethane sealant is 10 parts.
[0037] Example 9 The difference between Example 9 and Example 1 is that the amount of polyurethane sealant is 20 parts.
[0038] Example 10 The difference between Example 10 and Example 1 is that the amount of polyurethane sealant is 60 parts.
[0039] Embodiment 11 The difference between Example 11 and Example 1 is that the amount of polyurethane sealant is 80 parts.
[0040] Example 12 The difference between Example 12 and Example 1 is that the amount of polyurethane sealant is 120 parts.
[0041] Example 13 The difference between Example 13 and Example 1 is that the amount of polyurethane sealant is 150 parts.
[0042] Embodiments 14 to 26 correspond one to one with Embodiments 1 to 13, with the only difference being that Embodiments 1 to 13 are nickel-hydrogen batteries, and Embodiments 14 to 26 are nickel-zinc batteries.
[0043] Comparative Example 1 One part of carbon-supported palladium catalyst and 3 parts of 1,4-bis(phenylethynyl)benzene were added into an agate mortar and ground thoroughly to obtain a hydrogen absorption mixture; the process was carried out in a glove box filled with inert gas, and the grinding time was 8 hours.
[0044] The ground hydrogen absorption mixture is placed in a breathable sealed bag, which is placed in the shell of the nickel-hydrogen battery cell. When preparing the nickel-hydrogen battery, the insulating sheet at the bottom of the battery cell is simply dipped in polyurethane sealant, and the polyurethane sealant is evenly applied to the welding position between the positive electrode ear and the positive electrode sheet and the bottom plate of the positive electrode cap. After application, a UV lamp is used to heat the glue to accelerate the setting of the glue.
[0045] Comparative Example 2 The difference between Comparative Example 2 and Comparative Example 1 is that the nickel-metal hydride battery is replaced with a nickel-zinc battery.
[0046] The batteries of the above embodiments and comparative examples were tested, the nickel-hydrogen battery was subjected to a long-term floating charge test, and the nickel-zinc battery was subjected to a cycle life test.
[0047] Floating charge test: NiMH battery 2A1500 model was selected as the sample, and the bottom of the battery was drilled to expose the bottom pad, making sure that the battery pole group was not touched. Then the air column of the internal pressure tester was aimed at the battery hole and ensured that the two were tightly connected without air leakage. 0.1C charging was performed for 1 month, 2 months, and 3 months, and the internal pressure value was recorded.
[0048] Sealant performance test: Spot weld 2cm*0.5cm pure nickel strips on both ends of the positive and negative electrodes of the nickel-metal hydride battery, then connect the nickel-zinc battery to the positive and negative electrode fixtures of a 60V / 5A constant current source, completely immerse the connected battery in an uncovered box filled with oil, adjust the current to 1C, and record the time when the battery starts bubbling after the current stabilizes.
[0049] Table 1 Test data of nickel-hydrogen batteries in Examples 1 to 13 and Comparative Example 1
[0050] According to Table 1, Example 8 is the best example. The proportion of carbon-supported palladium catalyst and 1,4-bis(phenylethynyl)benzene in the hydrogen absorption material of Example 8 is high, so the hydrogen adsorption effect is the best and the internal pressure of the nickel-hydrogen battery is the lowest.
[0051] Compared with Example 8, the content of polyurethane sealant in Examples 9, 1, 10, 11, 12, and 13 increases successively, resulting in a decrease in the proportion of carbon-supported palladium catalyst and 1,4-bis(phenylethynyl)benzene, so the effect of hydrogen adsorption decreases successively, and the internal pressure of the nickel-hydrogen battery increases successively. In addition, in Examples 8 to 13, the content of polyurethane sealant increases successively, so the time for the battery to start bubbling gradually increases, indicating that the higher the proportion of carbon-supported palladium catalyst and 1,4-bis(phenylethynyl)benzene, the greater the impact on the sealing performance of the polyurethane sealant, so the number of polyurethane sealants should not be too small.
[0052] In Examples 1 to 5, the content of 1,4-bis(phenylethynyl)benzene in Example 5 is the highest, and the hydrogen absorption effect is the best. However, by comparison, it can be found that the hydrogen absorption effects of Example 1, Example 4, and Example 5 are not much different, indicating that 5 parts of 1,4-bis(phenylethynyl)benzene are sufficient to react with the catalyst; too much 1,4-bis(phenylethynyl)benzene not only cannot significantly improve the hydrogen absorption effect, but will increase the cost. In addition, in Examples 1 to 5, increasing the content of 1,4-bis(phenylethynyl)benzene will increase the time for the battery to start bubbling, indicating that increasing the content of 1,4-bis(phenylethynyl)benzene will improve the sealing performance of the polyurethane sealant to a certain extent. The reason may be that the electrolyte of the nickel-hydrogen battery is usually alkaline, and the structure of 1,4-bis(phenylethynyl)benzene contains hydrophobic phenyl and ethynyl groups, which helps to improve the water resistance of the polyurethane sealant in an alkaline environment, thereby improving the sealing performance of the polyurethane sealant. However, according to the time when the battery starts to bubble in Examples 1 to 5, it can be seen that the improvement of the sealing performance of the polyurethane sealant by 1,4-bis(phenylethynyl)benzene is relatively small. Therefore, appropriately reducing the proportion of carbon-supported palladium catalyst and 1,4-bis(phenylethynyl)benzene is most beneficial to improving the sealing performance of the polyurethane sealant.
[0053] In Example 6 and Example 7, the hydrogen-absorbing organic matter was replaced. Since the melting and boiling points of the two organic reagents, 1,4-diphenylbutadiyne and phenyl propargyl ether, are lower than 90°C, the battery temperature is above 80°C during the floating charge process, which easily causes 1,4-diphenylbutadiyne and phenyl propargyl ether to dissolve and volatilize, and fail to achieve the hydrogen absorption effect. Therefore, 1,4-diphenylbutadiyne and phenyl propargyl ether can only react with hydrogen when the battery temperature is low to achieve the hydrogen absorption effect. In addition, since both 1,4-diphenylbutadiyne and phenyl propargyl ether contain phenyl and ethynyl groups, the sealing of the hydrogen absorption material is not affected compared with Example 1.
[0054] Compared with Example 1, the hydrogen absorbing mixture is placed in a breathable sealed bag. Since the gas flowability in the sealed battery is poor and the hydrogen absorbing organic matter and the catalyst are unevenly distributed, the hydrogen absorbing effect is poor. In Example 1, the hydrogen absorbing material is applied at multiple locations in the battery, and the hydrogen absorbing organic matter and the catalyst are evenly distributed in the sealant, so the hydrogen absorbing effect is good.
[0055] Cycle life test: The nickel-zinc battery uses the 2A1400 model as the sample, uses a positive cap with a high pressure relief value of 4.0MPa, and seals the steel shell to 50.20mm. Due to the characteristics of the negative active material zinc dissolving and corroding in the alkaline electrolyte to produce hydrogen, the amount of hydrogen inside the nickel-zinc battery continues to increase. Faced with the positive cap with a high pressure relief value, the internal pressure cannot be released through the pressure relief valve, causing the internal pressure of the battery to be too high and the battery height to increase. The battery was subjected to a 1C charge and discharge accelerated cycle test at a high temperature of 60°C, and the height change of the battery after 100 and 200 cycles was recorded. The height change is shown in Table 2.
[0056] Sealant performance test: Spot weld 2cm*0.5cm pure nickel strips on both ends of the positive and negative electrodes of the nickel-zinc battery, then connect the nickel-zinc battery to the positive and negative electrode fixtures of a 60V / 5A constant current source, completely immerse the connected battery in an uncovered box filled with oil, adjust the current to 1C, and record the time when the battery starts bubbling after the current stabilizes.
[0057] Table 2 Battery test data table in Examples 16 to 30 and Comparative Example 2
[0058] According to Table 2, Example 21 is the optimal example. The proportion of carbon-supported palladium catalyst and 1,4-bis(phenylethynyl)benzene in the hydrogen absorption material of Example 21 is high, so the hydrogen adsorption effect is the best and the height change of the nickel-zinc battery is the smallest.
[0059] Compared with Example 21, the content of polyurethane sealant in Examples 22, 14, 23, 24, 25, and 26 increases successively, resulting in a decrease in the proportion of carbon-supported palladium catalyst and 1,4-bis(phenylethynyl)benzene, so the effect of hydrogen adsorption decreases successively, and the internal pressure of the nickel-zinc battery increases successively, so that its height increases successively. In addition, in Examples 21 to 26, the content of polyurethane sealant increases successively, so the time for the battery to start bubbling gradually increases, indicating that the higher the proportion of carbon-supported palladium catalyst and 1,4-bis(phenylethynyl)benzene, the greater the impact on the sealing performance of the polyurethane sealant, so the number of polyurethane sealants should not be too small.
[0060] In Examples 14 to 18, the content of 1,4-bis(phenylethynyl)benzene in Example 18 is the highest, and the hydrogen absorption effect is the best. However, by comparison, it can be found that the hydrogen absorption effects of Examples 14, 17, and 18 are not much different, indicating that 5 parts of 1,4-bis(phenylethynyl)benzene are sufficient to react with the catalyst; too much 1,4-bis(phenylethynyl)benzene not only cannot significantly improve the hydrogen absorption effect, but will increase the cost. In addition, in Examples 14 to 18, increasing the content of 1,4-bis(phenylethynyl)benzene will increase the time for the battery to start bubbling, indicating that increasing the content of 1,4-bis(phenylethynyl)benzene will improve the sealing performance of the polyurethane sealant to a certain extent. The reason may be that the electrolyte of the nickel-zinc battery is usually alkaline, and the structure of 1,4-bis(phenylethynyl)benzene contains hydrophobic phenyl and ethynyl groups, which helps to improve the water resistance of the polyurethane sealant in an alkaline environment, thereby improving the sealing performance of the polyurethane sealant. However, according to the time when the battery starts to bubble in Examples 14 to 18, it can be seen that the improvement of the sealing performance of the polyurethane sealant by 1,4-bis(phenylethynyl)benzene is relatively small. Therefore, appropriately reducing the proportion of carbon-supported palladium catalyst and 1,4-bis(phenylethynyl)benzene is most beneficial to improving the sealing performance of the polyurethane sealant.
[0061] In Example 19 and Example 20, hydrogen-absorbing organic substances were replaced. Since the melting and boiling points of the two organic reagents, 1,4-diphenylbutadiyne and phenyl propargyl ether, were lower than 90°C, the battery temperature was above 80°C during the cycle process, which easily led to the dissolution and volatilization of 1,4-diphenylbutadiyne and phenyl propargyl ether, and failed to achieve the effect of hydrogen absorption. Therefore, 1,4-diphenylbutadiyne and phenyl propargyl ether could only react with hydrogen when the battery temperature was lower to achieve the effect of hydrogen absorption.
[0062] Compared with Example 14, the hydrogen absorbing mixture is placed in a breathable sealed bag. Since the gas flowability in the sealed battery is poor and the hydrogen absorbing organic matter and the catalyst are unevenly distributed, the hydrogen absorbing effect is poor. In Example 14, the hydrogen absorbing material is applied at multiple locations in the battery, and the hydrogen absorbing organic matter and the catalyst are evenly distributed in the sealant, so the hydrogen absorbing effect is good.
[0063] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A hydrogen absorbing material, characterized in that: The invention comprises a sealant, a hydrogen absorbing organic substance distributed in the sealant, and a catalyst. The hydrogen absorbing organic substance contains one or more of alkenyl, alkynyl and phenyl groups. The catalyst is used for increasing the reaction rate of the hydrogen absorbing organic substance and hydrogen.
2. The hydrogen absorbing material according to claim 1, characterized in that The hydrogen absorbing organic matter is selected from C9~C 22 Benzene derivatives; And / or, the catalyst is selected from carbon-supported palladium catalyst.
3. The hydrogen absorbing material according to claim 2, characterized in that The hydrogen absorbing organic matter is selected from one or more of 1,4-bis(phenylethynyl)benzene, 1,4-diphenylbutadiyne and phenyl propargyl ether.
4. The hydrogen absorbing material according to claim 1, characterized in that The mass ratio of the catalyst to the hydrogen absorbing organic matter is 1:(1-5); The mass ratio of the catalyst to the sealant is 1:(20-150).
5. The hydrogen absorbing material according to claim 4, characterized in that The mass ratio of the catalyst to the hydrogen absorbing organic matter is 1:(2.5-3.5); The mass ratio of the catalyst to the sealant is 1:(20-60).
6. The hydrogen absorbing material according to claim 1, characterized in that The sealant includes one of polyurethane glue and organic silica gel.
7. A method for preparing a hydrogen absorbing material according to any one of claims 1 to 6, characterized in that: The following steps are involved: grinding the hydrogen absorbing organic matter and the catalyst to obtain a hydrogen absorbing mixture; The hydrogen absorbing mixture is added into the sealant and stirred to obtain the hydrogen absorbing material.
8. The preparation method according to claim 7, characterized in that: The grinding is carried out in an inert gas; And / or, the grinding time is 5-8h; And / or, the stirring temperature is 70-90° C., the stirring time is 1-2 h, and the stirring speed is 40-80 rpm / min.
9. A battery, characterized in that: It comprises a battery cell and the hydrogen absorbing material according to any one of claims 1 to 6; the hydrogen absorbing material is coated on the insulating sheet of the battery cell, the bottom plate of the positive electrode cap and / or the connection position between the electrode sheet and the electrode ear of the battery cell.
10. The battery according to claim 9, characterized in that The battery is a nickel-metal hydride battery or a nickel-zinc battery.
Citation Information
Patent Citations
Irreversible hydrogen-absorbing material, product and preparation method
CN101121116A
Irreversible hydrogen absorbing porous composite material preparation method and product thereof
CN110193361A
Polymer film material with hydrogen absorption function and preparation method thereof
CN112341822A
Block hydrogen absorption agent with efficient hydrogen absorption effect and preparation method thereof
CN115646158A
Manufacture of hydrogen absorbing alloy powder and electrode using hydrogen absorbing alloy powder obtained by this manufacturing method
JP1998074509A